Does Electricity Consumption have Significant Impact towards the Sectoral Growth of Cambodia? Evidence from Wald Test Causality Relationship - Nathan, Thurai Murugan; Liew, Venus Khim-Sen (Research Academy of Social Sciences, 2013)
It is recognized that energy-output relationship studies from an economic perspective have become popular among researchers recently. This study deals with the electricity consumption and outputs of some major economic sectors in Cambodia. The newly developed ARDL bound testing approach has been employed to examine the cointegration relationship. The Granger causality test of the aforementioned ARDL framework has also been used to investigate the corresponding causality effect. Analysis and discussion based on the data of Cambodia, for the period of 1980 to 2010, are presented. Interestingly, there is no any cointegration relationship identified between electricity consumption and sectoral outputs. But, causality effect has been identified from electricity consumption towards the sectoral outputs. Based on the findings, few recommendations have been made in the hope of systematizing the energy more efficiently within the scrutinized sectors.